2020
DOI: 10.3390/app10248824
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rainfall Intensity on the Stability of Unsaturated Soil Slope: Case Study of R523 Road in Thulamela Municipality, Limpopo Province, South Africa

Abstract: The purpose of this paper was to analyze the impact of extreme rainfall on the recurrence of slope instability using the Thulamela Municipality roads (R523) as a case study. To this end, the historical rainfall data of the area of study were analyzed between 1988 and 2018. The results show that a significant increase in rainfall is usually experienced in the summer months of December and January. Following this, the factor of safety (FoS) of slopes of silt clay, clay, and clay loam soils were estimated using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…is is because the exercise determined how realistic the computer model of the actual rock mass associated with the study area would be. For a thorough interpretation of the results, several methods (Bishop simplified, Corps of Engineers' #1 and 2, the GLE/ Morgenstern Price method, Janbu's simplified and corrected Lowe-K aralias, Ordinary, and Spencer) of analysis were considered (see studies such as [29,30,[32][33][34][35][36]). e motivation was to compare various approaches to the problem while corresponding results were interpreted based on the performance of each approach.…”
Section: Study Areamentioning
confidence: 99%
“…is is because the exercise determined how realistic the computer model of the actual rock mass associated with the study area would be. For a thorough interpretation of the results, several methods (Bishop simplified, Corps of Engineers' #1 and 2, the GLE/ Morgenstern Price method, Janbu's simplified and corrected Lowe-K aralias, Ordinary, and Spencer) of analysis were considered (see studies such as [29,30,[32][33][34][35][36]). e motivation was to compare various approaches to the problem while corresponding results were interpreted based on the performance of each approach.…”
Section: Study Areamentioning
confidence: 99%
“…It is observed that an increase in the water table will also increase water pore pressure, which pushes the soil particles away from each other, and hence reduces the stress between the particles resulting in soil slope failure. Two such papers [34,35] may be used as a guide to finding the adequate literature on the most used or the most advanced approaches followed in every step of the procedure for defining reliable rainfall thresholds. Figure 7 presents the factor of safety values achieved in the case of Material 1 for slope angle ranges from 70 to 88 degrees, respectively.…”
Section: Saturated Seismic Analysismentioning
confidence: 99%
“…In addition, several researchers [24][25][26][27][28][29][30][31] have examined the application of physical or empirical models on the impact of precipitation on slope stability. Most of them claimed that the effects of meteorological, morphological, and geological characteristics were mitigated.…”
Section: Introductionmentioning
confidence: 99%